2017
DOI: 10.1200/jco.2016.70.3934
|View full text |Cite
|
Sign up to set email alerts
|

Gefitinib and EGFR Gene Copy Number Aberrations in Esophageal Cancer

Abstract: Purpose The Cancer Esophagus Gefitinib trial demonstrated improved progression-free survival with the epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor gefitinib relative to placebo in patients with advanced esophageal cancer who had disease progression after chemotherapy. Rapid and durable responses were observed in a minority of patients. We hypothesized that genetic aberration of the EGFR pathway would identify patients benefitting from gefitinib. Methods A prespecified, blinded molecular an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 38 publications
(16 reference statements)
8
91
0
Order By: Relevance
“…Coamplification of ERBB2 and EGFR was not, however, required for afatinib response, as the combination of afatinib with trastuzumab showed modest clinical activity in ERBB2-amplified tumors lacking EGFR amplification. Furthermore, EGFR-selective inhibitors such as cetuximab and gefitinib have demonstrated activity in EGFR-amplified tumors lacking ERBB2 amplification, suggesting that these agents may have a different efficacy profile than afatinib (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Coamplification of ERBB2 and EGFR was not, however, required for afatinib response, as the combination of afatinib with trastuzumab showed modest clinical activity in ERBB2-amplified tumors lacking EGFR amplification. Furthermore, EGFR-selective inhibitors such as cetuximab and gefitinib have demonstrated activity in EGFR-amplified tumors lacking ERBB2 amplification, suggesting that these agents may have a different efficacy profile than afatinib (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for such failures is the lack of a predictive biomarker. This is illustrated in the COG study of gefitinib in esophageal carcinoma whereby, even though the overall study result was negative, a survival benefit was observed in a subgroup of patients with tumors amplified for EGFR …”
Section: Discussionmentioning
confidence: 99%
“…In fact, in a recent study of 22 pan-RAS/BRAF/HER2/MET wild-type colorectal carcinoma cases progressing on EGFR antibody therapeutic regimens, tissue and ctDNA analyses at cetuximab or panitumumab progression supported KRAS mutations and HER2 or MET amplification as the dominant mediators of clinical resistance (27). Furthermore, EGFR amplification is an emerging target in gastric and esophageal cancers (2931). However, in the relatively small analysis of paired samples in this study, no HER2 or MET amplifications (and just one EGFR amplification, found in tissue only) were observed in either subset, so concordance analysis was limited for these specific gene amplifications.…”
Section: Discussionmentioning
confidence: 99%